2.8 Metal-Catalyzed (5 + 1), (5 + 2), and (5 + 2 + 1) Cycloadditions - Li,X.; Tang,W. (Metal-Catalyzed Cyclization Reactions 2, 2016)
Metal-catalyzed (5 + n) cycloaddition is a powerful strategy for the synthesis of six-, seven-, and eight-membered carbocycles and heterocycles. These cycloadditions usually involve oxidative cyclization to a metallacycle; insertion into the C—M bond (e.g., by carbon monoxide, an alkene, alkyne, or allene, or a combination thereof); and reductive elimination. Vinylcyclopropanes and 3-acyloxy-1,4-enynes are the most common five-carbon synthons. Recent advances in transition-metal-catalyzed (5 + 1), (5 + 2), and (5 + 2 + 1) cycloadditions including their development, mechanistic studies, and applications are reviewed in this chapter.
Keywords: cycloaddition; transition metals; catalysis; vinylcyclopropanes; propargylic esters; (5 + 1) cycloaddition; (5 + 2) cycloaddition; (5 + 2 + 1) cycloaddition; carbocycles; heterocycles; seven-membered rings; alkenes; alkynes; allenes; imines; cyclopropanes; epoxides; rhodium; ruthenium; nickel; iron; dictamnol; aphanamol; allocyathin B2; tremulenediol A; tremulenolide A; pseudolaric acid B; frondosin A; rameswaralide; hirsutene; desoxyhypnophilin; asteriscanolide